HSES Knowledge Portal: Invention of Counting System - Miri, SK; Sahu, N (International Journal of Computer Sciences and Engineering, 2019)
The HSES Knowledge portal (www.hseshiksha.in) is designed and developed for the student, teacher and others who are teaching, learning and guiding in the higher secondary education sector of the India. In this portal, syllabus, eBooks, question papers and video lectures are ported for proving the study materials. Data is collected during the registration of new members and filling of feedback forms which is done online. A user can register anytime and anywhere all over India. Registered users can be filling the feedback form. Counting of users by locale, stream, board, gender, medium and state is difficult manually. It is possible with Microsoft Excel but time taking. Locale, stream, board, gender, and medium wise counting are possible through the counters which remove counting mistakes and saves time. In this portal, Counting of users have performed in this portal automatically which is the very challenging task. Invention of counting system for registered members of the HSES Knowledge Portal is beneficial for counting of users at locale, stream, board, gender and medium wise. It may aware green computing because persons take a lot of time to do it.